Application of Min-Max Stock Method in the optimization of auxiliary raw material inventory in the biodiesel industry - Amta, Indrian Saputra; Siregar, Masdania Zurairah; Lubis, Muhammad Fiza (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2024)
Inventory is an aspect of manufacturing operations to ensure the availability of raw materials while minimizing costs. PT. Permata Hijau Palm Oleo Belawan, a biodiesel company, faces challenges in balancing the inventory levels of key auxiliary raw materials such as Methanol, Catalyst, NaOH, Inventory is an aspect of manufacturing operations to ensure the availability of raw materials while minimizing costs. PT. Permata Hijau Palm Oleo Belawan, a biodiesel company, faces challenges in balancing the inventory levels of key auxiliary raw materials such as Methanol, Catalyst, NaOH, and HCl. Excessive inventory results in high storage costs, while inventory shortages can disrupt production continuity. This study aims to evaluate the effectiveness of the Min-Max Stock method in optimizing auxiliary raw material inventory at PT. Permata Hijau Palm Oleo Belawan, addressing its practical impacts on cost reduction and efficiency improvement in the palm oil-based biofuel industry. This study uses a quantitative approach, utilizing historical data on the purchase and usage of raw materials during the 2019-2020 period. The Min-Max Stock method is applied to determine the optimal inventory level, comparing the actual inventory level with the calculated minimum and maximum thresholds. The implementation of the Min-Max Stock method can save storage costs of around IDR 35 billion. The implementation of the Min-Max Stock method offers a solution that increases efficiency, reduces costs, and prevents production disruptionsand HCl. Excessive inventory results in high storage costs, while inventory shortages can disrupt production continuity. This study aims to evaluate the effectiveness of the Min-Max Stock method in optimizing auxiliary raw material inventory at PT. Permata Hijau Palm Oleo Belawan, addressing its practical impacts on cost reduction and efficiency improvement in the palm oil-based biofuel industry. This study uses a quantitative approach, utilizing historical data on the purchase and usage of raw materials during the 2019-2020 period. The Min-Max Stock method is applied to determine the optimal inventory level, comparing the actual inventory level with the calculated minimum and maximum thresholds. The implementation of the Min-Max Stock method can save storage costs of around IDR 35 billion. The implementation of the Min-Max Stock method offers a solution that increases efficiency, reduces costs, and prevents production disruptions